2015
DOI: 10.1039/c5ra15408a
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physico-chemical properties of insoluble rice bran fiber: effect of acid–base induced modifications

Abstract: Various acid–base regimes induced structural and physicochemical modifications of IRBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 32 publications
5
44
2
Order By: Relevance
“…A mass loss of about 10% was observed at 120 °C for all rice cultivars, which could be related to sample water loss, corroborating the moisture values obtained (Table 1). Accentuated mass loss was observed above 300 °C in all cultivars analyzed, which characterizes pyrolysis (Qi et al, 2015) and the beginning of thermal degradation.…”
Section: Resultsmentioning
confidence: 89%
“…A mass loss of about 10% was observed at 120 °C for all rice cultivars, which could be related to sample water loss, corroborating the moisture values obtained (Table 1). Accentuated mass loss was observed above 300 °C in all cultivars analyzed, which characterizes pyrolysis (Qi et al, 2015) and the beginning of thermal degradation.…”
Section: Resultsmentioning
confidence: 89%
“…However, the crystallinity of DBDF exhibited a significant increase (from 23.01% to 33.53%), which indicated that DHPM treatment exhibited a higher efficiency on the disruption of amorphous region, and most of starch, lignin and hemicellulose were removed (Luo et al ., 2018). The increase of crystallinity of fibre could improve its thermal stability, which contribute to the potential of using as reinforcing materials processed at high temperature (Qi et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, dietary fibres extracted from food processing by‐products are mostly insoluble fibres, which could adversely impact on the colour, texture, flavour, and taste in food products when they are incorporated in food products without any further modification (Robin et al ., 2012). Nowadays, these negative impacts would not be completely neutralized, but various modification methods have been applied to reduce them by modifying the particle size, surface area and microstructure of dietary fibres (Qi et al ., 2015; Ullah et al ., 2017; Liu et al ., 2018; Yang et al ., 2018). Among these methods, enzymatic hydrolysis and dynamic high‐pressure micro‐fluidisation (DHPM) have been proven to be effective and eco‐friendly compared to chemical methods traditionally used in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…White spots in Fig. 1 (c) are white agglomerates, which are removed by chemical modification of rice bran [40]. These modifications are the result of sulfonation and hydrolysis in the acidic environment.…”
Section: Mrb Characterizationmentioning
confidence: 99%